We know that
(a– b)2 = a2 + b2 – 2a×b
and (a+ b)2 = a2 + b2 + 2a×b
⇒ (a+ b)2 – (a– b)2 = (a2 + b2 + 2a×b) – (a2 + b2 – 2a×b)
⇒ (a+ b)2 – (a– b)2 = 4ab
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation